Neuropathic Pain-like Alterations in Muscle Nociceptor Function Associated with Vibration-induced Muscle Pain - Chen, Xiaojie (2010)
We recently developed a rodent model of the painful muscle disorders induced by occupational exposure to vibration. In the present study we used this model to evaluate the function of sensory neurons innervating the vibration-exposed gastrocnemius muscle. Activity of 74 vibration-exposed and 40 control nociceptors, with mechanical receptive fields in the gastrocnemius muscle, were recorded. In vibration-exposed rats ~15% of nociceptors demonstrated an intense and long-lasting barrage of action potentials in response to sustained suprathreshold mechanical stimulation (average of 2635 action potentials with frequency of ~44 Hz during a 1 minute suprathreshold stimulus) much greater than has been reported to be produced even by potent inflammatory mediators. While these high-firing nociceptors had lower mechanical thresholds than the remaining nociceptors, exposure to vibration had no effect on conduction velocity and did not induce spontaneous activity. Hyperactivity was not observed in any of 19 neurons from vibration exposed rats pretreated with intrathecal antisense for the IL-6 receptor subunit gp130. Since vibration can injure peripheral nerves, and IL-6 has been implicated in painful peripheral neuropathies, we suggest that the dramatic change in sensory neuron function and development of muscles pain, induced by exposure to vibration, reflects a neuropathic muscle pain syndrome.